Decision Support Systems from the Standpoint of Knowledge Representation - Degoulet, P.; Fieschi, M.; Chatellier, G. (Methods of Information in Medicine, 1995)
Relationships between decision-support systems and knowledge representation are examined from three different points of view: the characteristics of medical decisions that might influence the selection of appropriate knowledge representations, – the extent to which different knowledge representations can support efficient medical decisions and, – the validation of knowledge hypotheses through the practice of decision support systems. A three-level model of knowledge representation is proposed that includes a contextual, a conceptual and a computational level. Taking into consideration the context that leads to the selection of a given representation raises the issue of multiexpertise and multirepresentation modeling. Implementation of decision support systems as sets of cooperative agents and integration in the health information systems are considered.
Keywords: Decision-Support System; Epistemology; Knowledge Representation; Artificial Intelligence; Medical Decision